Strategi Pimpinan Gaya Transformasional Pada Kinerja Pegawai di Dinas Koperasi dan Usaha Mikro Kabupaten Kediri - Rahayuningsih, Lisa (DAS Institute, 2025)
Each leader has a program followed by strategic planning in the leadership process. The implementation of a transformational leadership style affects the performance of employees in government agencies, which also affects the implementation of ASN management. Because ASN is part of the Human Resources supporting the achievement of the vision and mission of government agencies. The research was conducted at the Kediri Regency Cooperative and Micro Business Office with the aim of analyzing the transformational style leadership strategy that can encourage employee performance to achieve work productivity as expected. This research method is qualitative, research instruments in the form of interview guidelines, data collection techniques with direct interviews. The interview technique is structured on a format that has been made by the researcher. The informants in this study were the head of the institutional and supervisory fields and the secretary of the Kediri Regency Cooperative and Micro Business Office. The results showed that the leadership has shown a leadership style in accordance with the four dimensions of leadership from Bernard M.Bass 1978. Then the strategy implemented encourages the improvement of the performance of employees who work in accordance with their jib description through: providing welfare to employees, encouraging employees to be disciplined at work, commitment to the organization which is shown by loyalty to work, employees need to be given a stimulus from outside as well for their welfare so that their commitment affects long-term performance improvement, organizations need to assist employees in improving their performance by involving professional development, welfare support, and creating a conducive work environment.